2012
DOI: 10.2106/jbjs.k.00460
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Prognostic Factors for a Consecutive Case Series of 115 Patients with Somatic Leiomyosarcoma

Abstract: Leiomyosarcoma is an aggressive disease, with a generally poor prognosis. Depth of tumor and high histological grade are indicators of a poor prognosis. Retroperitoneal tumors have a particularly high potential to metastasize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 19 publications
6
36
2
Order By: Relevance
“…Gladdy et al , in one of the larger series to date (353 patients with primary resectable LMS), found that although retroperitoneal location was associated with worse DSS compared to extremity or trunk tumors on univariate analysis, only grade and size (but not site of origin) were independent predictors of DSS and distant recurrence on multivariate analysis. Similarly, Abraham and colleagues , reporting on a series of 115 patients with somatic LMS (including soft tissue, retroperitoneal, vascular, and bone, but excluding uterine, gastrointestinal, and cutaneous forms), found that tumor grade, as well as depth and synchronous metastases (but not site of origin) were independent predictors of DSS.…”
Section: Discussionmentioning
confidence: 88%
“…Gladdy et al , in one of the larger series to date (353 patients with primary resectable LMS), found that although retroperitoneal location was associated with worse DSS compared to extremity or trunk tumors on univariate analysis, only grade and size (but not site of origin) were independent predictors of DSS and distant recurrence on multivariate analysis. Similarly, Abraham and colleagues , reporting on a series of 115 patients with somatic LMS (including soft tissue, retroperitoneal, vascular, and bone, but excluding uterine, gastrointestinal, and cutaneous forms), found that tumor grade, as well as depth and synchronous metastases (but not site of origin) were independent predictors of DSS.…”
Section: Discussionmentioning
confidence: 88%
“…Surgery is the cornerstone of treatment and is the only therapeutic modality proven to provide cure [ 5 ]. However, complete resection is often difficult due to large tumor size at presentation and recent studies have shown that resection margins may be the only significant predictor of local recurrence [ 4 , 15 ]. Moreover, complete primary surgical resection is critical for achieving the best overall outcome [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, complete primary surgical resection is critical for achieving the best overall outcome [ 16 ]. Other factors include tumor depth, histological grade, and metastasis at presentation [ 15 , 17 ]. The role of adjuvant chemotherapy in localized disease is not established and therefore is not standard treatment [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are microscopically similar to their deeper counterparts except that they are confined to the dermis with limited if any subcutaneous involvement, have a greater tendency for infiltrative rather than purely nodular growth, and have a lower incidence of tumor necrosis . Primary cutaneous leiomyosarcoma is considered a distinct disease entity from soft tissue or visceral leiomyosarcoma with an extremely low chance for metastasis, an indolent course and an excellent prognosis . Treatment is with wide local excision or Mohs micrographic surgery, and surgical margin status is the only predictor for recurrence .…”
Section: Discussionmentioning
confidence: 99%